Otimização dos parâmetros de soldagem a ponto por Fricção (FSpW) da liga AlMgSc e avaliação das propriedades mecânicas estáticas e dinâmicas - Lage, Sara Beatriz Miranda (Universidade Federal de São Carlos, 2017)
Aluminum alloys are widely used in transportation industry to reduce structural weight and fuel consumption. The development of advanced alloys and more effective technologies for joining materials contribute to achieve such objectives. AlMgSc alloys emerge as an interesting option to structural applications due to low density and high mechanical performance, as well as an attractive cost. Friction spot welding (FSpW) process is a novel solid state joining technology that has proven to be suitable for joining lightweight materials. This process is carried out in a few steps and in a short time with low thermal cycles and energy consumption as well as without extra materials addition. Thus, this process is an alternative to industrial techniques such as riveting and resistance spot welding. This work presents, for the first time, the application results of FSpW on AlMgSc sheets in overlapping configuration. The effect of the process parameters, such as rotational speed, plunge depth and plunge time, was investigated in order to obtain joints with higher lap shear strength. The Taguchi method and the analysis of variance were applied to study the influence of each parameter on mechanical properties of the joints. In addition, the welds were submitted to microstructural characterization and a material flow analysis provided an initial understanding about the formation of microstructural features. Therefore, the fatigue performance was analyzed for the condition of higher lap shear strength and the S-N curve was drawn. The results indicated a good static performance of the welds, although the fatigue performance was less satisfactory. Finally, failure mechanisms of static and dynamic tests seemed to be strongly related to geometric features, such as hook, bonding ligament and microstructural transition regions.
Optimization of friction spot welding (FSpW) process of AlMgSc alloy and evaluation of static and dynamic mechanical properties
Keywords: AlMgSc; Solda a ponto por fricção; FSpW; Método Taguchi; Resistência ao cisalhamento; Fadiga; Fratura; AlMgSc alloy; Friction spot welding; Taguchi Method; Lap shear strength; Fatigue; Fracture; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA